2002
DOI: 10.1051/parasite/2002094363
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of antibody response by Dot-ELISA in rabbits immunized with adultHaemonchus contortusantigen

Abstract: Summary:Whole adult soluble extract of Haemonchus contortus as an antigen along with Freund's complete adjuvant, was used to immunize rabbits. Antisera from immunized rabbits were collected at intervals of 30, 60, 90, 1 20, 1 50 and 1 80 days. For the detection and titration of anti-H. contortus antibodies in these sera, Dot-ELISA was developed. Sera collected 30 days postimmunization exhibited a litre of 1:5,000 in all the rabbits except one, where a titre of 20,000 was recorded. Later, all the rabbits attain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…In the present study in comparison to diffusion in gel, the ELISA test has been found to be highly effective and may be employed for the wide use in seroepidiomological survey (Ibarra et al, 1998) of paramhistomiasis. In Haemonchus contortus infection also a highest titre of 1:40, 000 observed with rabbit hyperimmune sera raised by somatic antigen of H. contortus (Kaur et al, 2002). The high titre observed in the present study may be the significance in diagnosis of paramhistomiasis in field.…”
Section: Discussionsupporting
confidence: 65%
“…In the present study in comparison to diffusion in gel, the ELISA test has been found to be highly effective and may be employed for the wide use in seroepidiomological survey (Ibarra et al, 1998) of paramhistomiasis. In Haemonchus contortus infection also a highest titre of 1:40, 000 observed with rabbit hyperimmune sera raised by somatic antigen of H. contortus (Kaur et al, 2002). The high titre observed in the present study may be the significance in diagnosis of paramhistomiasis in field.…”
Section: Discussionsupporting
confidence: 65%